Pengaruh Model Inquiry-Based Learning terhadap Kemampuan Berpikir Taktis dalam Permainan Sepakbola pada Siswa SMA - Syahruddin, Syahruddin (Program Studi Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effect of the application of the Inquiry-Based Learning (IBL) learning model on students' tactical thinking skills in soccer games at SMA 9 Makassar. The research method used a quasi-experimental design with a pretest–posttest control group design. The sample consisted of 40 students divided into two groups: 20 students in the experimental group (IBL) and 20 students in the control group (conventional method). The instruments were a tactical performance test through soccer games and a tactical observation sheet (notational analysis). Data were analyzed using normality tests, homogeneity tests, paired t-tests, and independent t-tests. The results showed that the experimental group experienced an average increase in tactical thinking skills from 62.40 (pretest) to 81.25 (posttest), while the control group increased from 63.10 to 69.30. The t-test results confirmed that the increase in the experimental group was statistically significant (p < 0.01) compared to the control group. These findings indicate that the IBL model is significantly effective in improving tactical thinking skills in soccer games compared to conventional methods. Practical implications: Physical education teachers and school coaches may consider implementing IBL to train students' cognitive-tactical aspects, not just technical or motor skills. This research supports the idea that active-participatory learning can develop young soccer players who are not only physically skilled but also able to think strategically in real-life games.